(untitled) (Journal of the College of Basic Education, 2022)
Bashar Ibn Burad is a blind poet. He grew up in the Umayyad era and became famous during the Abbasid era. He wrote a lot of poetry, especially in spinning and satire, and the Abbasid caliph (Mahdi) ordered his death after he The poet is over seventy years of age (1). As for the reason for his killing, many attribute it to accusing him of heresy and obscenity in his poetry. There might be Other issues, one of which is Bashar’s satire of the Mahdi’s minister, Ya’qub ibn Dawood, which was the cause of the minister’s hatred. him, which prompted him to tarnish his image in front of the caliph.